Analysis of K3 Compliance Level in PT X Using Behavior-Based Safety Method - Mulawarman, Alif; Kemit, Ag Hael Woka; Kawung, Ferlix Flenix; Putra, M. Abiyyu; Katutu, M. Nazar; T.B, Mathias Novrian; Mesoino, Joshua Reiner Hans (Riviera Publishing, 2024)
PT X is one of the companies engaged in transportation/freight forwarding services. Transportation Management Services, which are the concentration of PT X, are closely related to containers where this work activity risks the safety and health of work and can potentially cause hazards, ranging from the loading-unloading process shipping to storage. Therefore, a study on occupational safety and health (K3) is needed. Container shipping service companies, given several sources, focus on developing facilities and technology to improve service quality and operational efficiency. The facilities provided by container shipping service companies include complete resting places, other supporting facilities, and other supporting infrastructure. They also pay attention to price indicators appropriate to the services provided and acceptable to consumers. This research uses the BBS method (Behavior Based Safety), a proactive accident prevention effort focusing on dangerous behavior that can potentially cause accidents. In this way, BBS seeks to reduce work accidents by identifying and reducing unsafe behavior by workers and increasing awareness of potential dangers that result in incidents and accidents.